Metalloprotease Dependent Release of Placenta Derived Fractalkine - Monika Siwetz; Astrid Blaschitz; Julia Kremshofer; Jelena Bilic; Gernot Desoye; Berthold Huppertz; Martin Gauster (Mediators of Inflammation)
The chemokine fractalkine is considered as unique since it exists both as membrane-bound adhesion molecule and as shed soluble chemoattractant. Here the hypothesis was tested whether placental fractalkine can be shed and released into the maternal circulation. Immunohistochemical staining of human first trimester and term placenta sections localized fractalkine at the apical microvillous plasma membrane of the syncytiotrophoblast. Gene expression analysis revealed abundant upregulation in placental fractalkine at term, compared to first trimester. Fractalkine expression and release were detected in the trophoblast cell line BeWo, in primary term trophoblasts and placental explants. Incubation of BeWo cells and placental explants with metalloprotease inhibitor Batimastat inhibited the release of soluble fractalkine and at the same time increased the membrane-bound form. These results demonstrate that human placenta is a source for fractalkine, which is expressed in the syncytiotrophoblast and can be released into the maternal circulation by constitutive metalloprotease dependent shedding. Increased expression and release of placental fractalkine may contribute to low grade systemic inflammatory responses in third trimester of normal pregnancy. Aberrant placental metalloprotease activity may not only affect the release of placenta derived fractalkine but may at the same time affect the abundance of the membrane-bound form of the chemokine.